Perancangan dan Implementasi Controller Knowledge Base pada Pengendalian Kecepatan Motor Induksi Tiga Fasa - Almasri, Almasri; Santoso, Agus (Lembaga Penelitian Universitas Negeri Padang, 2008)
Designing a controller, the model development is necessary. From the model will shown the relationship between plant response and models response expected. This research will try to make plant of controller which has relationship between plant response and the models response. From the plant response and models response will be made the rule base as the basic plant of knowledge based controller. Before making the rule base, the plant parameters must be identified. The plant of knowledge based will be implemented for controlling three phase motor induction directly. From the relationship between plant response and the expected model. It’s easier to use knowledge based controller to mean some models we expected. The aim of this research is to obtain algorithms of knowledge base controller non-lenear base plant and model response expected, so that is obtained realtion really between the second response, which can controlled lenear and non-lenear plant and the stability of speed of the three phases induction motor is constant although change of load. Key Word : knowledge based controller, rule base, three phase motor induction